This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let f ( x ) = a x 3 + b x 2 + c x + d . Substitute the 4 given coordinates into f ( x ) , and you will get this system of equations:
⎩ ⎪ ⎪ ⎪ ⎨ ⎪ ⎪ ⎪ ⎧ f ( − 1 ) = 3 f ( − 2 ) = − 1 2 f ( 0 ) = 6 f ( 2 ) = 2 4 − a + b − c + d = 3 − 8 a + 4 b − 2 c + d = − 1 2 0 a + 0 b + 0 c + d = 6 8 a + 4 b + 2 c + d = 2 4 ⟹ d = 6
Substitute the value of d into the remaining 3 equations, and you should have
⎩ ⎪ ⎨ ⎪ ⎧ − a + b − c = − 3 − 8 a + 4 b − 2 c = − 1 8 8 a + 4 b + 2 c = 1 8 ⟹ 1 ⟹ 2 ⟹ 3
2 + 3 :
( − 8 a + 4 b − 2 c ) + ( 8 a + 4 b + 2 c ) = − 1 8 + 1 8 8 b = 0 b = 0
Substitute the value of b into 1
− a + 0 − c = − 3 ⟹ a = 3 − c ⟹ 4
Substitute the value of b and 4 into 3 :
8 ( 3 − c ) + 4 ( 0 ) + 2 c = 1 8 2 4 − 8 c + 2 c = 1 8 6 c = 6 c = 1 ⟹ a = 3 − 1 = 2
The function is f ( x ) = 2 x 3 + x + 6 . Therefore,
f ( f ( 1 ) ) = f ( 2 ( 1 ) 3 + 1 + 6 ) = f ( 9 ) = 2 ( 9 ) 3 + 9 + 6 = 1 4 7 3